Catalysing the way towards antimicrobial effectiveness: A systematic analysis and a new online resource for antimicrobialenzyme combinations against Pseudomonas aeruginosa and Staphylococcus aureus - Jorge, Paula Alexandra Silva (2019)
Growing antimicrobial resistance and biofilm infection resilience have led researchers to study the potential laying in antimicrobial combinations, including those encompassing enzymes with biofilm disrupting abilities. Therefore, this work set out to evaluate the undergone journey of antimicrobial enzyme combination research and gain insights into its current status and most promising leads. Expert curators annotated and analysed all published experimental data on enzyme-encompassing combinations for two major biofilm-forming pathogens, Pseudomonas aeruginosa and Staphylococcus aureus. This entailed the construction of the first publically accessible online database on antimicrobial enzyme combinations, the Antimicrobial Enzyme Combinations Database (www.ceb.uminho.pt/aecd). Gathered data was also reconstructed as knowledge-networks to help analyse and visualize annotated entities (e.g. enzymes, methods, strains, combination outputs). The database currently holds 122 and 206 annotated combinations for P. aeruginosa and S. aureus, respectively, and their analysis allowed a systematic review of the available evidence on enzyme combinations, reliably illustrating the studies being performed. The most tested enzymes (e.g. lysozyme, DNAse, lysostaphin) were scrutinised and the rationale behind each combination explained. This research area is still growing even though current research gaps/opportunities were identified, such as lack of biofilm testing and of studies on polymicrobial scenarios. Hopefully, this work will shed light on the synergetic potential resting in enzyme combinations and alleviate some of the time and resource-consuming tasks related to enzyme combination research by helping the selection and design of new enzyme related therapeutic options for P. aeruginosa and S. aureus infections.